PENGARUH RELATIONSHIP MARKETING DAN KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN - putri, della asmaria; Sari, Yosi Puspita (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2025)
This study aims to determine the extent of the influence of Relationship Marketing and Service Quality on Customer Loyalty, with Customer Satisfaction as an Intervening Variable, at Bank BRI Unit Painan. Data collection was carried out through a survey method by distributing questionnaires to 100 respondents. The data were analyzed using multiple linear regression and path analysis with the help of SPSS software. Based on the partial test (t-test) results, it was found that Relationship Marketing and Service Quality have a significant effect on Customer Satisfaction. Furthermore, Relationship Marketing, Service Quality, and Customer Satisfaction have a significant influence on Customer Loyalty. However, Customer Satisfaction does not act as a mediating variable between Relationship Marketing and Customer Loyalty. Meanwhile, Customer Satisfaction does mediate the relationship between Service Quality and Customer Loyalty. The contribution of the independent variables, namely Relationship Marketing and Service Quality, to the dependent variable Customer Satisfaction is 49.9%, while the remaining 51.1% is influenced by other factors not included in this study. Meanwhile, the contribution of Relationship Marketing, Service Quality, and Customer Satisfaction to Customer Loyalty is 24.0%, with the remaining 74.4% influenced by other variables beyond the scope of this research.